2007
DOI: 10.1200/jco.2006.08.1075
|View full text |Cite
|
Sign up to set email alerts
|

Phase III Trial of Capecitabine Plus Oxaliplatin As Adjuvant Therapy for Stage III Colon Cancer: A Planned Safety Analysis in 1,864 Patients

Abstract: XELOX has a manageable tolerability profile in the adjuvant setting. Efficacy data will be available within the next 24 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
151
2
9

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(177 citation statements)
references
References 16 publications
15
151
2
9
Order By: Relevance
“…Toxicity profiles of FOLFOX and FOLFIRI (Andre et al, 2004;O'Connell, 2004;Allegra and Sargent, 2005) may reduce the completion of these treatments, but fewer cycles of these regimes may be as efficacious as the completed Mayo regime. A recently published safety analysis of the XELOX NO16968 study (Schmoll et al, 2007) found more frequent treatment discontinuations with XELOX compared to the FU/LV Mayo and Roswell Park regimes; however a comparable number of patients completed 12 weeks of therapy (88 and 82%, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Toxicity profiles of FOLFOX and FOLFIRI (Andre et al, 2004;O'Connell, 2004;Allegra and Sargent, 2005) may reduce the completion of these treatments, but fewer cycles of these regimes may be as efficacious as the completed Mayo regime. A recently published safety analysis of the XELOX NO16968 study (Schmoll et al, 2007) found more frequent treatment discontinuations with XELOX compared to the FU/LV Mayo and Roswell Park regimes; however a comparable number of patients completed 12 weeks of therapy (88 and 82%, respectively).…”
Section: Discussionmentioning
confidence: 95%
“…Despite recent advances in the development of various diagnostic tools, in many patients, colorectal cancer is still diagnosed at an advanced stage, and recurrent tumors are often detected even after curative surgery. On the other hand, new chemotherapeutic regimens such as FOLFOX, FOLFIRI, and XELOX have been developed to exert a more potent activity 3, 4, 5, 6. More recently, molecular targeted therapies such as tyrosine kinase inhibitors and monoclonal antibodies have been shown to enhance tumor regression in combination with chemotherapy 7, 8…”
mentioning
confidence: 99%
“…More importantly, our study provides preliminary survival data to support the efficacy of XELOX in the adjuvant setting. There are two published trials showing a favourable survival outcome and tolerability associated with the use of XELOX in the adjuvant setting (Schmoll et al, 2007;Haller et al, 2011). However, our study contained a wider range of standard (non-trial) patients than in controlled clinical studies, thus better representing the reality of everyday clinical practice.…”
Section: Discussionmentioning
confidence: 99%